Cross-cultural validation of health literacy measurement tools in Italian oncology patients - Paola Zotti; Simone Cocchi; Jerry Polesel; Chiara Cipolat Mis; Donato Bragatto; Silvio Cavuto; Alice Conficconi; Carla Costanzo; Melissa De Giorgi; Christina A. Drace; Federica Fiorini; Laura Gangeri; et al. (BMC, 2017)
Abstract Background The aim of this study was to assess the psychometric characteristics of four Health Literacy (HL) measurement tools, viz. Newest Vital Sign (NVS), Short Test of Functional Health Literacy in Adults (STOFHLA), Single Item Literacy Screener (SILS) and Single question on Self-rated Reading Ability (SrRA) among Italian oncology patients. Methods The original version of the tools were translated from the English language into Italian using a standard forward-backward procedure and according to internationally recognized good practices. Their internal consistency (reliability) and validity (construct, convergent and discriminative) were tested in a sample of 245 consecutive cancer patients recruited from seven Italian health care centers. Results The internal consistency of the STOFHLA-I was Chronbach's α=0.96 and that of NVS-I was α=0.74. The STOFHLA-I, NVS-I, SILS-I and SrRA-I scores were in a good relative correlation and in all tools the discriminative known-group validity was confirmed. The reliability and validity values were similar to those obtained from other cultural context studies. Conclusion The psychometric characteristics of the Italian version of NVS, STHOFLA, SILS and SrRA were found to be good, with satisfactory reliability and validity. This indicates that they could be used as a screening tool in Italian patients. Moreover, the use of the same cross-cultural tools, validated in different languages, is essential for implementing multicenter studies to measure and compare the functional HL levels across countries.